2021
DOI: 10.1371/journal.pone.0245870
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ≥high-grade anal intraepithelial lesions in MSM living with HIV and the response to topical and surgical treatments

Abstract: Background The objective of this study in MSM living with HIV was to determine the incidence of HSIL and ASCC, related factors, and the response to treatment. Patients and methods Data were gathered in 405 consecutive HIV-infected MSM (May 2010-December 2018) at baseline and annually on: sexual behavior, anal cytology, and HPV PCR and/or high-resolution anoscopy results. They could choose mucosectomy with electric scalpel (from May 2010) or self-administration of 5% imiquimod 3 times weekly for 16 weeks (fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, these data must be interpreted with caution because very few cases with HPV-18-VL and HSILs have been studied, and so these results are difficult to extrapolate. Notwithstanding, other studies have suggested that HPV-18 could also be a useful biomarker for the detection of anal lesions ( Hidalgo-Tenorio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, these data must be interpreted with caution because very few cases with HPV-18-VL and HSILs have been studied, and so these results are difficult to extrapolate. Notwithstanding, other studies have suggested that HPV-18 could also be a useful biomarker for the detection of anal lesions ( Hidalgo-Tenorio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…electrocautery (overall complete and partial response rates for imiquimod, 5-FU, and electrocautery were 46%, 42%, and 69%, respectively) and Grade 3-4 adverse events common in the topical treatment groups (43% in the imiquimod and 27% in the 5-FU group), [14,15]. However, a recent small, single center, longitudinal cohort study of MSM living with HIV and diagnosed with HSIL found excellent response rates and tolerability of imiquimod with less recurrence compared to surgical treatment [4]. In a systematic review of 14 studies of intraanal imiquimod, complete response in 211 patients with HSIL was observed in 35%, partial response 20.9% and recurrence in 15% [16].…”
Section: Plos Onementioning
confidence: 97%
“…Local recurrence or new, metachronous anal HSIL may occur with all treatment modalities, especially as the underlying persistent HPV infection may not be cured. Smoking, poor HIV control (low CD4 cell count or HIV viremia), persistent infection with HPV16/18 or chronic mixed HPV infections can increase the risk for recurrent disease [2][3][4]. Novel approaches to expand the therapeutic armamentarium against HPV related anogenital dysplasia are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding anal dysplasia, several prospective cohorts have reported a relationship between a low nadir CD4 lymphocyte count and a higher risk for HSIL [ 96 , 97 ]. Indeed, a retrospective study cohort comprising 2800 HIV-infected male or female patients reported a lower risk of progression of LSIL to HSIL among those who presented virological suppression (defined as HIV RNA levels <400 copies/mm 3 ) or CD4 lymphocyte counts >350 cells/µL [ 98 ].…”
Section: Relationship Between Antiretroviral Therapy and Hpvmentioning
confidence: 99%